برنامج کالیبرCailber المجانى لادارة وتنظیم الکتب الالکترونیة دراسة تعریفیة تقییمیة تطبیقیة على الاستخدام فى مکتبات الأدیرة المسیحییة مع وضع خطة تطبیقیة لتعمیم الاستخدام بالهیئات / المؤسسات بالدول العربیة - د. تریزا ولیم عزمى William Azmi (المجلة الدولية لعلوم المكتبات والمعلومات)
Study aims at Identification of Caliber, An electronic program formanagement & organizing of E-Books. The Study includes many sections, Firstof them is the theoretical section which includes methodology of the studyrepresented in (Introduction, Importance of the study, Justifications of choosingthe subject, Queries of the study, Tools of data gatherings, Previous studies)Then the study moved to the practical side represented as definitive assessmentof the program and its advantages, rather than it is a free program.